APPLICATION OF SIX SIGMA TECHNOLOGY TO HYBRID MANUFACTURING PROCESSES APPLIED RESEARCH IN BAGHDAD COMPANY FOR SOFT DRINKS - Alyaa Mohammed Khaleel; Bushra Sabeeh Kadhim; Aisha Hammody Hashim (Scholar Express Journals, 2022)
The aim of the research is to present the methodology of the research sample company to apply the requirements of hybrid manufacturing using a checklist that includes the following paragraphs (quality, cost, productivity, waiting time and service level). And the application of the six sigma approach to reduce defects in its production processes. Through a checklist that consists of paragraphs (commitment and support of senior management, training and reward and recognition system, organization culture, financial capabilities and statistical and technical tools). In order to know the actual reality, identify the gap and work to reduce this gap. The importance of this research stems from the importance of providing a theoretical and conceptual framework. A practical application of using two methodologies to help economic units improve the quality of their products and reduce the costs of poor quality. The research reached a set of conclusions. The most important of which is that the company is able to implement this system significantly. Through the results shown by the checklist and the availability of dimensions or performance measures for this system in the company.
Keywords: six sigma; hybrid manufacturing processes; productivity